NIRA review: a journal of opinion on public policy worldwide - National Institute for Research Advancement (Japan); Center for Policy Research Information (Tokyo National Institute for Research Advancement, 1999)
​
NIRA Review is a quarterly journal of debate and analysis on current policy research worldwide. It is edited by the Center for Policy Research Information. Two issues only are available at the libray
Keywords: Political Science; POLITICAL ECONOMY; Financial economics; Public policy; INTERNATIONAL COOPERATION; PERIODICALS